Identity Negotiation of Expatriates (High-Skilled Immigrants) in the Context of Intercultural Communication in Work Environment - Winna Ananda SURAKHMAD; Mirza RONDA; Dewi WIDOWATI (International Journal of Environmental, Sustainability, and Social Science, 2023)
In the industry world, a successful business is highly dependent on effective globalization (Toomey, 1999:4). And effective globalization is linked with diverse workforce, workers who come from diverse cultural backgrounds. This opens up many opportunities, especially for high-skilled immigrants or expatriates, but at the same time it also provides room for uncertainty in how individuals construct their identities. This uncertainty may trigger tension between individuals in their daily interactions. This study aimed to determine how high-skilled immigrants carry out identity negotiation in a culturally diverse work environment. The framework of thought in this research was mainly Stella Ting-Toomey's theory of identity negotiation. The method used in this research was phenomenology. The primary data of this study were the results of interviews with employees in culturally diverse companies and were supported by secondary data in the form of direct observations at the research site. The main findings of this study include how the values of a culturally diverse company provide climate that supports the identity negotiation process among high-skilled immigrant individuals within it.